Belonging : the meaning and future of Canadian citizenship - Kaplan, William, 1957- (McGill-Queen's University Press, 1993)
Belonging is about the past, present, and future of Canadian citizenship. Several contributors deal with the quality of Canadian citizenship and the principle of distributive justice applied to all. Others offer a "lament" for the Canadian nation, analyzing and explaining why the vision of Canadian citizenship as an allegiance to the federation did not succeed in overcoming the varied loyalties pulling Canadians in different directions. Some authors celebrate this failure, arguing that holding dual alliance to the nation and province is more important. The essays reflect a consensus that Canada and Canadians have failed to give their citizenship meaning. One explanation for this, offered by William Kaplan, is that Canadians are private about their patriotism, even if it is deeply felt.